Current and new targets for treating myositis. (August 2022) - Moghadam-Kia, Siamak; Oddis, Chester V.
Abstract: As treatment of refractory idiopathic inflammatory myopathies (IIM) has been challenging, there is growing interest in assessing new therapies that target various pathways implicated in the pathogenesis of IIM. In the largest clinical trial to date, rituximab was studied in adult and juvenile myositis, but the primary outcome was not met despite 83 percent of subjects with refractory myositis meeting the definition of improvement. The U.S. Food and Drug Administration (FDA) has recently granted approval to Octagam 10% immune globulin intravenous (IVIg), for the treatment of adult dermatomyositis based on impressive results from a double-blind placebo-controlled trial. Anti-tumor necrosis factor (anti-TNF) utility in IIM is not recommended and recent reports suggest this therapy may induce systemic autoimmune disease including myositis. Further, anti-IL6 therapy cannot be recommended as a recent trial of tocilizumab failed to reach its primary endpoint. Further studies are needed to assess the role of newer therapies such as abatacept (inhibition of T cell co-stimulation), sifalimumab (anti-IFNα), Janus kinase [JAK] inhibitors, apremilast (phosphodiesterase 4 inhibitor), and KZR-616 (selective inhibitor of the immunoproteasome) given their biological plausibility and encouraging recent small-case series results. The future of IIM therapy will depend on exploring biomarkers implicated in the etiopathogenesis of IIM, improvements in myositis classification based on serological and histopathological features, and well-designed controlled clinical trials using validated consensus outcome measures.